Pengaruh Kepercayaan Merek, Desain Produk Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada UD KVN Keripik Tape Bondowoso - Tri Resa Febrian; Budi Santoso; Pawestri Winahyu (Jurnal Manajemen DIVERSIFIKASI, 2025)
The business environment in Indonesia is becoming more competitive on a daily basis, particularly in the food industry, because every UD operating in the culinary sector is trying to increase market share and reach new consumers. One type of business that is still the center of attention of all groups is the culinary industry. The presence of UD KVN Tape Chips in Bondowoso Regency where currently this product is selling well on the market, because it is a new product and this product does not lose the characteristic taste of the tape, making this tape chip very phenomenal on the market at the moment. In this study, consumer satisfaction at UD KVN Bondowoso Tape Chips is to be measured and analyzed in relation to the effects of product design, service quality, and brand trust. The research design that is being employed is descriptive quantitative. In this study, 80 responders made up the sample. Using SPSS version 26, multiple linear analysis is the technique that is employed. The coefficient of determination test results indicate that 67.5% of consumer happiness is influenced by brand trust, product design, and service quality. The findings of the t test indicate that at UD KVN Bondowoso Tape Chips, consumer satisfaction is significantly impacted by brand trust, product design, and service quality.